DRAINLESS COMBINED METHOD FOR WATER DESALINATION AND ITS PARTIAL SOFTENING - H. G. Feyziyev; G. H. Huseynova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents  an operational mode of the combined technology pertaining to preparation of partially softened water used for thermal networks and deeply softened make-up water for installation of a reverse osmosis with H- and Na-cation exchange. Depending on ionic composition of initial water and a consumption ratio of water fed to a thermal network and a consumption of make-up water which is fed to an installation of the reverse osmosis calculation formulas for regenerations of H- and Na-of ions in the cation-exchange filters have been given in the paper.